The Authority of the Acting Regent in the Process of Mutation of Acting Primary High Leaders - Siwalette, Anthoni; Saptenno, Marthinus Johanes; Bakarbessy, Andress Deny (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: The Acting Regent and Acting Mayor in carrying out their duties obtain permission from the Minister of Home Affairs to carry out Mutation and Rotation of Civil Servants for Primary High Leadership Positions and for Administrator Officials, the main thing that is considered and the reason for the Acting Regent to carry out mutations and rotations according to him, is so that the implementation of local government can run more effectively, but this policy reaps many pros and cons.Purposes of the Research: This research aims to determine the legal regulations regarding the authority of the Acting Regent in the process of transferring Primary High Leadership officials in West Seram Regency, and the legal consequences if the mutation process of Primary High Leadership Officials is not in accordance with the process and authority stipulated in the regulatory provisions legislation.Methods of the Research: This research aims to determine the legal regulations regarding the authority of the Acting Regent in the process of transferring Primary High Leadership officials in West Seram Regency, and the legal consequences if the mutation process of Primary High Leadership Officials is not in accordance with the process and authority stipulated in the regulatory provisions legislation.Results Main Findings of the Research: The authority of the Regional Government in appointing Primary High Leadership Positions is regulated by Law Namber 23/2014. Meanwhile, the prohibition on Acting Regional Heads from transferring employees is regulated in Law Number 5 of 2014 concerning State Civil Apparatus, Article 130A, Article 130, so that Regent Officials in making employee transfer decisions have legal consequences. Furthermore, the legal consequences of the policy of the Acting Regent of West Seram Regency in carrying out employee transfers are inappropriate.